Sex and age-related patterns in pediatric primary headaches: observations from an outpatient headache clinic - Faria, Vanda; Höfer, Berit; Klimova, Anna; von der Hagen, Maja; Berner, Reinhard; Sabatowski, Rainer; Koch, Thea; Hübler, Anke; Richter, Matthias; Moulton, Eric A.; Holmes, Scott A.; Gossrau, Gudrun (Frontiers in Neurology, 2024)
Background Age reportedly affects headache prevalence differently in boys and girls. However, little empirical data exists regarding pediatric headache prevalence and headache-related burden in children and adolescents according to age and sex. In the present study, we considered age and sex while evaluating the distribution, characteristics, and impairment of primary headache disorders at a pediatric headache center in Germany. Methods Medical records of children and adolescents attending the headache clinic of the Interdisciplinary Pain Center of the Carl Gustav Carus University Hospital in Dresden during the period 2015–2022 were retrospectively grouped and analyzed depending on age (< or ≥14 years) and sex. Results The study population consisted of 652 children and adolescents, aged between 3 and 18 years. Almost two-thirds of the patients (≈60%) were females, and almost two-thirds of these females (58%) were ≥14 years of age. Generally, the most prevalent headache diagnoses as defined by the International Classification of Headache Disorders 3rd edition were episodic migraine without aura and the combination of tension-type headache and episodic migraine with or without aura i.e., mixed-type headache (each ≈27%). In the younger group (<14 years), the mixed-type headache was the most prevalent in girls (28.6%), whereas, for boys, episodic migraine without aura was the most prevalent headache diagnosis (47.4%). In the older group (≥14 years), the mixed-type headache continued to be the most prevalent for girls (30%), and it became the most prevalent for boys (26.3%). Before the age of 14, about 16% of children were severely affected by their headaches. After the age of 14, this proportion increased to roughly one-third (33%) of adolescents, driven mainly by teenage girls (26%) who were severely affected by their headaches. Furthermore, the prevalence of comorbidities was significantly higher among girls (67%), particularly in the adolescent group (74%). Conclusions Our data shows that headache disorders in a specialized pediatric clinic impose a significant burden, especially among teenage girls indicating high therapy needs. Enhancing awareness of early diagnosis and preventive care is crucial to mitigate the development of chronic headaches, and mitigate their adverse effects on life quality and educational capability.